SOME ISSUES OF SAFETY IN THE USE OF TOWER CRANES USED IN CONSTRUCTION PROJECTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the relevance of design solutions in construction work, and in particular the maintenance of safety distances in the design of the correct choice of assembly cranes, in particular, the solution of labor protection and safety issues on technological maps in the learning process, increase production efficiency and reduce construction costs is displayed.